Linkages Between Brain Size and Language Capacity - Simbolon, Sanris Lawanti; Harahap, Rosmawaty (PT Inovasi Pratama Internasional, 2024)
The organ in the human body that controls all movements and functions, including language, is the brain. The cerebrum, especially the left hemisphere, is crucial for language activities. The human left brain is a domain that functions as a place of concentration and as a regulator and controller of language abilities. The left hemisphere also appears to be involved in sign language processing, similar to how it is involved in non-signers. The right brain is also involved in complex ways but differently for sign language users. Studies on brain and language continue to develop and have shown significant progress. However, findings sometimes appear inconsistent, particularly regarding the involvement of the right brain in language. Many studies suggest that the second language can sometimes be located in the right brain, though this is not always the case. There may be variables that determine the brain's language localization, but these have not yet been fully identified. One factor may be the age at which the second language is learned, as well as the unique growth and development of each individual.